Review Xtuple Enterprise Resource Planning (ERP) PostBooks Edition 4.0.0 - Guntara, Agun (Infoman's, 2019)
Open source ERP has now grown rapidly, its use has been used by many different types of businesses, whether it's a small, medium, and large-scale companies. One product ERP opensource i.e. xtuple postbooks edition, edition of xTuple ERP is targeted towards small and medium sized companies. ERP application provides sub systems for accounting, sales, CRM, Purchasing, inventory, Industry and products. This product is light to use, because the size of the application is only 83 MB